Population genetic structure and demographical history of South African abalone, Haliotis midae, in a conservation context - Van der Merwe, Aletta Elizabeth (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Genetics))--University of Stellenbosch, 2009.